NF-κB and Its Regulators During Pregnancy - Gómez-Chávez, Fernando; Correa, Dolores; Navarrete-Meneses, Pilar; Cancino-Diaz, Juan Carlos; Cancino-Diaz, Mario Eugenio; Rodríguez-Martínez, Sandra (Frontiers in Immunology, 2021)
The transcriptional factor NF-κB is a nuclear factor involved in both physiological and pathological processes. This factor can control the transcription of more than 400 genes, including cytokines, chemokines, and their modulators, immune and non-immune receptors, proteins involved in antigen presentation and cell adhesion, acute phase and stress response proteins, regulators of apoptosis, growth factors, other transcription factors and their regulators, as well as different enzymes; all these molecules control several biological processes. NF-κB is a tightly regulated molecule that has also been related to apoptosis, cell proliferation, inflammation, and the control of innate and adaptive immune responses during onset of labor, in which it has a crucial role; thus, early activation of this factor may have an adverse effect, by inducing premature termination of pregnancy, with bad outcomes for the mother and the fetus, including product loss. Reviews compiling the different activities of NF-κB have been reported. However, an update regarding NF-κB regulation during pregnancy is lacking. In this work, we aimed to describe the state of the art around NF-κB activity, its regulatory role in pregnancy, and the effect of its dysregulation due to invasion by pathogens like Tricomonas vaginalis and Toxoplasma gondii as examples.